2016
DOI: 10.1002/ajmg.c.31501
|View full text |Cite
|
Sign up to set email alerts
|

Special cases in Cornelia de Lange syndrome: The Spanish experience

Abstract: Cornelia de Lange Syndrome (CdLS) is an autosomal dominant (NIPBL, SMC3, and RAD21) or X-linked (SMC1A and HDAC8) disorder, characterized by distinctive craniofacial appearance, growth retardation, intellectual disability, and limb anomalies. In 2005, the Spanish CdLS Reference Center was started and now we have more than 270 cases in our database. In this special issue, we describe some of the unique or atypical patients studied by our group, whose clinical features have contributed to the expansion of the Cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Somatic mosaicism in NIPBL is frequent in CdLS patients and might further contribute to the different expression of symptoms among patients [3][4][5]. Furthermore, even in the presence of variants affecting the same causative gene, a wide clinical spectrum, from classical to mildly affected patients, is known [6]. The cohesin complex is not only involved in sister chromatids cohesion, but it also exhibits novel biological functions, such as the regulation of gene transcription [7][8][9], thus extending the range of pathomechanisms relevant for cohesinopathies and potentially explaining the variability in the clinical manifestations of CdLS [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Somatic mosaicism in NIPBL is frequent in CdLS patients and might further contribute to the different expression of symptoms among patients [3][4][5]. Furthermore, even in the presence of variants affecting the same causative gene, a wide clinical spectrum, from classical to mildly affected patients, is known [6]. The cohesin complex is not only involved in sister chromatids cohesion, but it also exhibits novel biological functions, such as the regulation of gene transcription [7][8][9], thus extending the range of pathomechanisms relevant for cohesinopathies and potentially explaining the variability in the clinical manifestations of CdLS [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In CdLS patients negative for germline mutations, mosaic alterations can be detected. Due to the high sensitivity of the method, NGS seems to be the most appropriate technique to identify such variants (17, 19). To date, several patients with mosaic variants in CdLS-related genes have been reported (17, 20, 21).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous study, approximately 20% of NIPBL variants are located within intron sequences (19). In this study, three splice site variants have been identified in the NIPBL gene in four patients, three with classic CdLS and one with a mild phenotype (mosaic splice site variant).…”
Section: Discussionmentioning
confidence: 99%
“…Up to 70% of clinically diagnosed CdLS patients harbor heterozygous pathogenic variants in NIPBL gene (OMIM 608667) ( 5 , 6 ) which encodes a regulatory protein loading the cohesin complex onto sister chromatids. More than 300 pathogenic variants, mostly point mutations, have been found evenly spread across the whole NIPBL gene in CdLS patients ( 4 , 7 ). Frameshift variants, the most prevalent NIPBL defects, commonly underlie a severe phenotype, while pathogenic missense variants are often associated to mild disease ( 8 ).…”
Section: Introductionmentioning
confidence: 99%